Factors Influencing Agency Costs in the Publicly Listed IT Firms: Evidence from Bangladesh - Muntaqim Chowdhury; Imroz Mahmud; Md. Mehrabul Hoque (Jurnal Bisnis dan Keuangan, 2023)
The primary goal of this research is to identify the factors that influence agency costs in publicly listed IT firms in Bangladesh. The research is based on secondary data obtained from nine IT firms listed on the Dhaka Stock Exchange (DSE) between 2018 and 2021, providing thirty-five firm-year observations. The effects of eight independent factors: board size, firm size, female directors, independent directors, managerial ownership, foreign ownership, institutional ownership, and leverage are examined in this study. For measuring the agency costs, the Asset Utilization Ratio (AUR) and Expense Ratio (EXR) have been employed as proxies. An ordinary least square (OLS) regression model has been used to test the hypothesized model. The study findings indicate that managerial ownership and institutional ownership are inversely and significantly associated with agency costs. In contrast, the board size, independent directors, and foreign ownership have a direct and significant relationship with agency costs. However, the relationship between agency costs and leverage or firm size cannot be determined. Besides, no statistically significant association has been found between female directors and agency costs. Being the first of its kind, the research findings can assist policymakers figure out what causes agency costs in IT firms and then take the right steps to reduce them.